Sabung ayam sebagai bentuk praktik judi oleh remaja - Dira Sakila; Susi Fitria Dewi; Maria Montessori; Eni Kurniawati (Journal of Education, Cultural and Politics, 2026)
Sabung ayam is a form of deviant behavior still practiced by some youth in Pasie Nan Tigo Village, having evolved into gambling. This study aims to discuss the practice of cockfighting, focusing on examining cockfighting among youth in Pasie Nan Tigo Village, identifying factors that lead youth to become involved in cockfighting, and analyzing efforts made by authorities to address the practice. This study employed a qualitative descriptive method. The research location was in Pasie Nan Tigo Village. Data collection consisted of field observations, in-depth interviews with informants, and document collection in the form of photographs of activities at the research site. Data validity was tested using data triangulation, with data analysis techniques including data reduction, data presentation, and conclusion drawing. The results of the study indicate that sabung ayam among teenagers in Pasie Nan Tigo Village is a form of social deviation carried out secretly in fields to avoid legal monitoring, where this activity has become a social identity for the perpetrators. Factors causing adolescent involvement include: a) Economic factors, namely the desire to get money instantly to fulfill a consumptive lifestyle, b) Peer factors, c) Factors of lack of tolerance from society so that teenagers seek real solidarity through sabung ayam. This study also found several efforts made by the youth leader, Babinsa (village supervisor), and the village government.